Precision location sensors for ambient assisted living - Tey, Timothy Tong Zhi (Nanyang Technological University, 2023)
Research on IoT applications have led to the development of AAL Devices. AAL devices are important as the population grows older, a large percentage of the elderly spend their time alone at home. To give the Elderly a modicum of safety and security, an inexpensive UWB indoor RTLS system was proposed.